Application of botulinum toxin associated with aesthetic surgical crown lengthening in treatment of gummy smile (Journal of Face Aesthetics, 2023)
The pursuit of esthetic excellence has become a major goal in the dental treatment. The beauty of the smile is not only constituted by the shape, position and size of the teeth, but also based on the characteristics of the gingival tissue and conformation of the lips, which should be as harmonious as teeth. Gummy smile is one of the complaints of the patients, since such a situation can influence self-esteem. The purpose of this article is to present the case of a patient who presented dentogingival discrepancy and gummy smile, treated by gingivectomy and by application of botulinum toxin.
Keywords: botulinum toxins type A; dental esthetics; gingival overgrowth; gingivectomy; gummy smile